Inhibitory effects of two types of food additives on biofilm formation by foodborne pathogens. Issue 9 (9th June 2019) - Liu, Liyan; Ye, Congxiu; Soteyome, Thanapop; Zhao, Xihong; Xia, Jing; Xu, Wenyi; Mao, Yuzhu; Peng, Ruixin; Chen, Jinxuan; Xu, Zhenbo; Shirtliff, Mark E.; Harro, Janette M.
Abstract: The inhibition of microbial biofilms is a significant concern in food safety. In the present study, the inhibitory effect of sodium citrate and cinnamic aldehyde on biofilm formation at minimum inhibitory concentrations (MICs) and sub‐MICs was investigated for Escherichia coli O157:H7 and Staphylococcus aureus . The biofilm inhibition rate was measured to evaluate the effect of sodium citrate on S. aureus biofilms at 24, 48, 72, and 96 hr. According to the results, an antibiofilm effect was shown by both food additives, with 10 mg/ml of sodium citrate exhibiting the greatest inhibition of S. aureus biofilms at 24 hr (inhibition rate as high as 77.51%). These findings strongly suggest that sodium citrate exhibits a pronounced inhibitory effect on biofilm formation with great potential in the extension of food preservation and storage. Abstract : In this study, firstly, we have observed the ability of biofilm formation by test bacteria ( Staphylococcus aureus and Escherichia coli O157:H7) as well as the growth trends via Congo red plate method and Crystal violet staining respectively. Secondly, we determined the minimum inhibitory concentrations (MICs) of two kinds of food additives (sodium citrate and cinnamic aldehyde) for the S . aureus strains and E. coli strains separately, and then we investigated their inhibitory effects on biofilm formation by test bacteria at both MICs and sub‐MICs. Finally, the results showed the biofilm inhibition rate of sodium citrate against S. aureus strains was the highest (10 mg/ml), which was 77.51% at 24 hr in S. aureus strains.